Saussurea costus alleviates ulcerative colitis by regulating the gut microbiota and improving intestinal barrier integrity - Wen-lin Pang; Wen-lin Pang; Tian-gang Li; Tian-gang Li; Yin-ying Wang; Yin-ying Wang; Li-yun Song; Li-yun Song; Li Li; Li Li; Xiao-ya Li; Xiao-ya Li; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionThe global health challenge of ulcerative colitis (UC) has been classified by the WHO as a modern refractory disease, commonly referred to as green cancer, with limited treatment options still available, highlighting the urgent need for the development of new therapeutic strategies. Recent pharmacological research has shown that traditional Chinese medicine saussurea costus (SC) possesses beneficial antibacterial and anti-inflammatory properties. Nevertheless, its underlying mechanism remains elusive.MethodsFirstly, we identified the main active components of SC through UHPLC-QTOF-MS analysis. Subsequently, UC mice were induced using DSS and administered different doses of SC to evaluate its efficacy. Additionally, the impact of SC on the repair of the intestinal mucosal barrier was evaluated through immunofluorescence and western blot. Furthermore, 16s rRNA gene sequencing was conducted to elucidate the contribution of gut microbiota to UC pathogenesis.ResultsThe primary components of SC include Proline, Phenylalanine, Isoleucine, Lucidenic acid M, and Pyroglutamic acid. The efficacy of SC was concurrently assessed, revealing its potential to ameliorate histological injury in colitis mice. Furthermore, SC was found to decrease levels of TNF-α, IL-1β, IL-8, and IL-18 while promoting the expression of IL-10 and IL-22. Similarly, we also found that the expression of ZO-1 and Occludin was reversed by SC in colitis mice. In addition, analysis of 16S rRNA gene sequencing indicated that SC reduced harmful bacterial populations, such as Proteobacteria, while simultaneously enhancing the levels of beneficial bacteria like Lactobacillus, thereby contributing to the improvement of UC pathology.ConclusionThis study highlights the therapeutic potential of SC in managing UC through its ability to attenuate inflammatory responses, restore intestinal barrier functionality, and modulate gut microbiota composition, which findings offer insights into potential strategies for advancing UC treatment.